2019
DOI: 10.1242/jcs.231878
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ entry via TRPC1 is essential for cellular differentiation and modulates secretion via the SNARE complex

Abstract: Properties of adipocytes, including differentiation and adipokine secretion, are crucial factors in obesity-associated metabolic syndrome. Here, we provide evidence that Ca 2+ influx in primary adipocytes, especially upon Ca 2+ store depletion, plays an important role in adipocyte differentiation, functionality and subsequently metabolic regulation. The endogenous Ca 2+ entry channel in both subcutaneous and visceral adipocytes was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…For instance, Orai1-STIM1-mediated Ca 2+ entry promotes the activation and nuclear translocation of the NFAT (nuclear factor of activated T-cells) transcription factor, while a TRPC1-dependent Ca 2+ entry is responsible for NF-κB transcription factor activation in human submandibular gland cells [71]. STIM1-Orai1-TRPC1-mediated Ca 2+ entry is also required for platelet aggregation [72], insulin release [73], adipocyte differentiation and adiponectin secretion [74], among other functions. Moreover, STIM1-Orai1-TRPC1-dependent Ca 2+ currents have been associated to the Ca 2+ mobilization responsible for the development of distinct cancer hallmarks in different cancer cell types, including prostate cancer cells [75] and colon cancer cells [76,77], while STIM1-Orai1-TRPC1-TRPC4-mediated Ca 2+ currents are involved in the Ca 2+ remodelling involved in hypertrophic cardiomyopathy in rat ventricular myocytes [78].…”
Section: Trpc Channels In the Stim1-orai1 Scenariomentioning
confidence: 99%
“…For instance, Orai1-STIM1-mediated Ca 2+ entry promotes the activation and nuclear translocation of the NFAT (nuclear factor of activated T-cells) transcription factor, while a TRPC1-dependent Ca 2+ entry is responsible for NF-κB transcription factor activation in human submandibular gland cells [71]. STIM1-Orai1-TRPC1-mediated Ca 2+ entry is also required for platelet aggregation [72], insulin release [73], adipocyte differentiation and adiponectin secretion [74], among other functions. Moreover, STIM1-Orai1-TRPC1-dependent Ca 2+ currents have been associated to the Ca 2+ mobilization responsible for the development of distinct cancer hallmarks in different cancer cell types, including prostate cancer cells [75] and colon cancer cells [76,77], while STIM1-Orai1-TRPC1-TRPC4-mediated Ca 2+ currents are involved in the Ca 2+ remodelling involved in hypertrophic cardiomyopathy in rat ventricular myocytes [78].…”
Section: Trpc Channels In the Stim1-orai1 Scenariomentioning
confidence: 99%
“…We have demonstrated that TRPC1 -/-animals have reduced adipocyte differentiation, reduced markers for autophagy, and increased expression of apoptosis markers, suggesting a change in neutral lipid storage and the sphingomyelin-ceramide pathway regulating nutrient transport, cell proliferation, and apoptosis (13,14). We also demonstrated lower adipose mass in HFD fed TRPC1 -/-mice when compared to HFD fed WT mice (11,15). When provided access to exercise, HFD fed TRPC1 -/-mice experienced greater loss of adipose by mass and reduced insulin resistance compared to WT animals under the same conditions, indicating TRPC1 plays a role in systematic energy homeostasis, particularly neutral lipid metabolism.…”
Section: Introductionmentioning
confidence: 59%
“…We have demonstrated that adipose proliferation is reduced in mice by knocking-out transient receptor potential canonical channel 1 (TRPC1) ( 11 ). TRPC1, a ubiquitous member of the transient receptor potential superfamily, is an integral membrane protein that regulates Ca 2+ ion flux across the membrane ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ is necessary for cell proliferation and G 1 is the most sensitive phase of the cell cycle to Ca 2+ depletion [ 34 ]. Intracellular Ca 2+ concentrations and calcium signaling pathways are important factors in regulating cell proliferation and differentiation [ 35 , 36 ]. Intracellular Ca 2+ activates the MAPK pathway and resultantly participates in stem cell differentiation into lineages [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%